2010
DOI: 10.1021/tx100188b
|View full text |Cite
|
Sign up to set email alerts
|

Ability of Hypochlorous Acid and N-Chloramines to Chlorinate DNA and Its Constituents

Abstract: Myeloperoxidase is a heme enzyme released by activated phagocytes that is responsible for the generation of the strong oxidant hypochlorous acid (HOCl). Although HOCl has potent bactericidal properties and plays an important role in the human immune system, this oxidant also causes damage to tissues, particularly under inflammatory conditions. There is a strong link between chronic inflammation and the incidence of many cancers, which may be associated with the ability of HOCl and related oxidants such as N-ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
67
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 63 publications
0
67
0
Order By: Relevance
“…In most cases, the metabolic process is accomplished without injury to the liver itself, whereas many xenobiotic compounds are toxic that can cause liver injury [9]. Accumulating evidence has shown that chloramine-T causes oxidative stress by inducing the generation of reactive oxygen species (ROS) [15]. Sakuma et al (2009) found that monochloramine could increase ROS generation in the cytoplasm of rat primary hepatocyte cultures [12].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In most cases, the metabolic process is accomplished without injury to the liver itself, whereas many xenobiotic compounds are toxic that can cause liver injury [9]. Accumulating evidence has shown that chloramine-T causes oxidative stress by inducing the generation of reactive oxygen species (ROS) [15]. Sakuma et al (2009) found that monochloramine could increase ROS generation in the cytoplasm of rat primary hepatocyte cultures [12].…”
Section: Discussionmentioning
confidence: 99%
“…· http://ucom.ru/nm · ISSN 2500-2031 · HOCl and the model N-chloramine are able to chlorinate cellular genetic material, which may play a role in the development of various inflammatory cancers [15]. They have examined the ability of various N-chloramines to form chlorinated base products on nucleosides, nucleotides, DNA, and in cellular systems [15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MPO also produces chlorinating species that react with DNA to form chlorinated adducts such as 5-chloro-2′-deoxycytidine (5-Cl-dC) (23), the presence of which was identified in colon tissue of H. hepaticus-infected Rag2 −/− mice (10). This modification of DNA may provide a mechanistic link between neutrophil activity and colitis-associated carcinoma (10,24,25).…”
mentioning
confidence: 99%